Arbitration, mediation and cheap talk - Maria Goltsman; Johannes Hörner; Gregory Pavlov; Francesco Squintani (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2007)
We compare three common dispute resolution processes - negotiation, mediation, and arbitration - in the framework of Crawford and Sobel (1982). Under negotiation, the two parties engage in (possibly arbitrarily long) face-to-face cheap talk. Under mediation, the parties communicate with a neutral third party who makes a non-binding recommendation. Under arbitration, the two parties commit to conform to the third party recommendation. We characterize and compare the optimal mediation and arbitration procedures. Both mediators and arbitrators should optimally filter information, but mediators should also add noise to it. We find that unmediated negotiation performs as well as mediation if and only if the degree of conflict between the parties is low.
Keywords: 330; Konflikt; Mediation; Schiedsgerichtsbarkeit; Verhandlungen